The Impact of Local Road Infrastructure on Driver Safety: A Systematic Literature Review - Hartati, Noviar Dwi; Puspitasari, Nina Ripka; Muizz, Fikri Abdul; Rijaluddin , Arief; Taufik, Mohamad (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Although human movement and economic growth depend on adequate road infrastructure, unsafe construction can have a detrimental effect on safety. Road crashes, a major global public health issue, necessitate research into multifactorial causes, including driver behavior, vehicle performance, and infrastructure. This study employs a Systematic Literature Review (SLR) to identify key infrastructure factors affecting safety, assess research consistency, and pinpoint knowledge gaps. Using Google Scholar, Publish or Perish, and VOSviewer, secondary data from scientific journals (2000-2025) were analyzed. Results indicate